NILAI MANTRA GAWAI DAYAK KALIMANTAN BARAT - Widiyarto, Sigit; Pujaning Ati, Aster; Hadi, Irfan; Saputri, Nia Liska; Luluk Setyowati (BASASTRA: JURNAL KAJIAN BAHASA DAN SASTRA INDONESIA, 2024)
Literature is a noble work that needs to be preserved for the continuity of the valuestaught to future generations. Preservation can be done by understanding and studying the valuescontained in literature itself. The Dayak gawai mantra is a mantra full of noble values forgenerations and important lessons for life. The aim of this research is to describe the valuescontained in the Mantra for the Dayak gawai ceremony of the Kantuk tribe which is carried outevery year, in addition to describing what equipment is used in this tradition. The method used isa descriptive qualitative method with an ethnographic approach. The method also usestriangulation techniques to verify data. Data collection was carried out by interviews,documentation and distribution of questionnaires. The research results show that the value of theGawai Dayak Mantra is related to divinity and respect for nature as well as the values of unityand equality. The equipment used includes sesjen (traditional food and drinks) and kitchenutensils and farming equipment.